The Role Of Road Safety Inspection Towards Ensuring Forgiving Roads In Malaysia - Hameed, Azreen Arifah Shahul (Universiti Sains Malaysia, 2022)
Accidents are commonly constructed by many reasons such as uncontrolled vehicle speed, poor road conditions, and irresponsible driving, such as reckless driving and drunk driving. A civil engineer must pay attention to every road feature to manage these challenges. After construction, the safety of the roads must be maintained. Transportation and development in Malaysia are becoming more intense and sophisticated than ever, partly as a result of population growth and increase in vehicles ownership. This makes road safety a challenging and complex issue. This study research attempts to understand Road Safety Inspection's (RSI) role in ensuring forgiving roads in Malaysia. This project compares the RSI guidelines established by the Malaysian Institute Road Safety Research (MIROS) with The World Road Association (PIARC), executes RSI hands-on at the selected site, and analyses the road user's perspective to determine the significance of RSI in ensuring forgiving roads in Malaysia. Overall, the research study shows that the guidelines by MIROS are more suitable to be used especially in Malaysia because it is beginner-friendly as the methods of inspection are explained in detail. In addition, from the RSI conducted on the inspection area, there are a few flaws on the road that can be amended by following the remedial measures suggested. Moreover, the respondents’ perspective on road safety in the inspected area matches with the analysis from RSI conducted on the site like the need to install streetlights, repaint the road markings, and, more. Therefore, Road Safety Inspection (RSI) has a role that is relevant to ensuring the roads in Malaysia is forgiving as it can understand the conditions of the road that is viewed by the road users and evaluate the safety of the condition can reduce the potential of road accidents.